Pengaruh Staffing Sebagai Salah Satu Fungsi Manajemen di Mitra Jaya Company Terhadap Kinerja Karyawan - Siti Azizah; Hanivan Sabtaji (MAMEN: Jurnal Manajemen, 2022)
Mitra Jaya Company is a company located in Malang City and is engaged in animal husbandry by producing egg incubators. The descriptive statistical analysis and multiple linear regression analysis methods were used in this study. Based on these result, the recruitmen, selection, training, reward and punishment, as well as development simultaneously have huge impact on Mitra Jaya Company employee performance. The t-test results show a t-Cal 2,936  as well as a significance value 0,007 between the recruitment variable and the employee performance variable. Based on these results, the recruitmen have huge impact on Mitra Jaya Company employee performance. The t-test between the selection variable and the employee performance variable yielded a t-Cal 2,228  and a significance value 0.036 . Same as recruitment, the selection variables have huge impact on Mitra Jaya Company employee performance. The training variable's t-test generated t-Cal -0,149, with a significant value 0,883, indicating that the training variable has no impact on employee performance. Then t-test results on the reward and punishment variable including development obtained a t-Cal 1.699, with such a significant value 0,102 and a t-Cal 0.531 with significant value 0,601. Based on these results, the reward, punishment and development variables have no huge impact on Mitra Jaya Company employee performance.